Gamalnorsk *mǫð f. ‘slåtteeng’ i norske stadnamn - Samuele Mascetti (Namn og Nemne)
Danish and Swedish mad(e) m. ‘flood-meadow’ (cognate of e.g., German Matte and English meadow) presupposes PN *madu and ON *mǫð f., but such a common noun is unattested. Nonetheless, a few Norwegian oeconyms are interpreted as developments of *mǫð f. in Norske Gaardnavne. An in-depth analysis of their toponymic environments shows that they probably originated as names of hayfields in relation to earlier settlements. Therefore, we can assume that *mǫð f. was one of the many ON words for grassland (cf. engjar f. pl., vin f., ló f./n., fit f., etc.). The eventual disappearance of *mǫð could be due to competition from more common synonyms as engjar f. pl. and ey f. ‘meadow next to a body of water’. The hypothetical derivative *mǽði n. is also discussed, but while formally possible, its existence is improbable due to a dubious empirical background and overall lack of corresponding formations outside of West Norse.